Combustion processes - Lewis, Bernard, 1899-1993 (High speed aerodynamics and jet propulsion, 1956)
Volume II of the High Speed Aerodynamics and Jet Propulsion series. This volume includes treatments of all aspects of combustion necessary to the development of jet and rocket engines. Originally published in 1956. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.